PENGARUH BUDAYA ORGANISASI, KOMPENSASI, MOTIVASI DAN KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PT. ANGKASA PURA I (Persero) BANDARA INTERNASIONAL SULTAN AJI MUHAMMAD SULAIMAN (SAMS) SEPINGGAN BALIKPAPAN - Hasan, Syahril (Jurnal Benefita, 2016)
The purpose of this study was to determine the effect of variable of organizational culture, compensation, motivation and leadership simultaneously on the performance of employees, and which of those variables that have a dominant influence partially on the performance of employees of Angkasa Pura I (Persero) International Airport Sultan Aji Muhammad Sulaiman (SAMS) Sepinggan, PT            Results of analysis of regression equation: Y = 3.961 + 0.160 X1 + 0.425 X2 + 0.127 + 0.257 X3 X4. Equation model of multiple regression analysis indicated the effect of each independent variable on the dependent variable, which is indicated by the regression coefficient of each independent variable.            Simultaneously variable organnisasi culture, compensation, motivation and leadership have significant influence on employee performance. This is evidenced by comparing Fhitung which amounted to 56.505 compared with Ftabel amounting 2.430 R square value is equal to 0.601, meaning that the variable of organizational culture (X1), compensation (X2), motivation (X3), and leadership (X4) has contributed 0.601 or 60.1% of the rise and fall on employee performance. While the remaining 40.9% is influenced by other variables that are not included in this study. For variables that have the most dominant influence is evidenced compensation variable compensation has the biggest t is 5.349. Then the second hypothesis proved to be true.